Estimating financial information asymmetry in real estate transactions in China - An application of two-tier frontier model. Issue 2 (March 2022) - Pu, Ganlin; Zhang, Ying; Chou, Li-Chen
Highlight: Price dispersion in housing market is explained by estimating the degree of information ignorance buyers and sellers. Price discrimination strategy set by house suppliers is due to their considerably high bargaining abilities in the market In case of Zhejiang Province of China, price discrimination strategy made the transaction price 4.86% higher than the reasonable price. Information asymmetry estimation in Zhejiang real estate transaction shows Hangzhou had the largest net surplus in housing transaction market, followed by Jinhua, Ningbo, and Wenzhou Abstract: This study applies the two-tier stochastic frontier model to estimate the distribution of housing transaction information in Hangzhou, Wenzhou, Ningbo, and Jinhua (four cities in Zhejiang Province, China) during the year 2018, to analyze the difference in the price information acquired by the buyers and sellers in the transaction, and the effect of information asymmetry on the transaction price. The empirical results show that in each city, during the housing transaction process, the supplier has more complete information about house prices than consumers, and can therefore implement price discrimination strategies in setting service prices. Due to the disadvantage in acquired information, consumers on average need to pay a price 4.86% higher than a reasonable transaction price. In addition, the information asymmetry problem in urban areas is relatively more serious than in other areas. In terms of comparisons between cities, Hangzhou had the largest net surplus in the housing transaction market, followed by Jinhua, Ningbo, and Wenzhou.